The Analysis of Students' Metacognitive Skills in Physics through Problem-Solving Strategies in Physics Education Students - Heppy Sapulete; Fryan Sopacua; Venty Sopacua (Postgraduate, University of Mataram, 2024)
This study aims to analyze the metacognitive skills of students through problem-solving learning strategies in the subject of Basic Physics 1. The research sample consists of students enrolled in the Basic Physics 1 course in the Physics Education Study Program at Pattimura University, Ambon, for the 2023/2024 academic year. This study uses a descriptive quantitative and qualitative research type, with a one-shot case study design. The instruments used in this research include: (1) A questionnaire to assess students' metacognitive skills, (2) An observation sheet to observe students' problem-solving activities, and (3) A student response questionnaire to evaluate students' responses to problem-solving learning. Data analysis in this study is conducted using descriptive quantitative analysis to describe the data as is in percentage form and explain the data or events qualitatively with explanatory sentences. The data analysis techniques used include descriptive quantitative analysis, which covers the results of the metacognitive skills questionnaire, observations of problem-solving activities, and the response questionnaire. The results of the metacognitive skills questionnaire showed a percentage of 57.58%, categorized as fairly good. The student response to problem-solving learning received a percentage of 52.27%, categorized as fairly good. The observation of problem-solving activities yielded a percentage of 57%, also categorized as fairly good